Physical activity levels after low anterior resection for rectal cancer: one-year follow-up - Anne Asnong; André D'Hoore; Albert Wolthuis; Yves Van Molhem; Bart Van Geluwe; Annouschka Laenen; Nele Devoogdt; An De Groef; Tessa De Vrieze; Charlotte Van Calster; Inge Geraerts (BMC, 2021)
Abstract Background Overall survival rates after rectal cancer have increased. Therefore, functional outcomes rightly deserve more interest. The aims of this study were to assess progression in total, sports, occupational and household physical activity levels of rectal cancer survivors, from preoperatively to 12 months after surgery/stoma closure and to explore predictive factors. Methods Multi-center prospective study with 125 patients who underwent low anterior resection for rectal cancer. The Flemish Physical Activity Computerized Questionnaire was completed concerning all physical activity levels at baseline (past preoperative year) and at 1, 4, 6 and 12 months after surgery/stoma closure. At these timepoints, questionnaires (LARS−/ COREFO-questionnaire) regarding bowel symptoms were also filled out. Results were analyzed using linear mixed models for repeated measures. Results Total physical activity levels up to 12 months remained significantly lower than preoperative. Occupational and sports physical activity levels remained significantly lower until 6 and 4 months postoperative, respectively. Predictive factors for decreased physical activity levels at a specific timepoint were: younger age and no stoma (total physical activity, 1 month), low/mid rectal tumor, no stoma, non-employed status (total, 4 months), higher COREFO-scores (occupational, 4 months) and non-employed status (total, 12 months). At all timepoints, lower COREFO-scores were associated with higher total physical activity levels; male gender and lower educational levels with higher occupational levels; younger age, normal BMI, employed status and adjuvant therapy with higher sports levels; and female gender, lower educational level and unemployed status with higher household levels. Conclusions One year after rectal cancer treatment, total physical activity levels were still not recovered. Rectal cancer patients, especially those at risk for decreased physical activity levels and with major bowel complaints, should be identified and guided to increase their activities. Trial registration This trial has been registered at Netherlands Trial Register ( NTR6383 , 23/01/2017).